Mediating role of self-efficacy in the relationship between family functioning and self-management behaviors in patients with coronary heart disease: A cross-sectional study in Jiangsu, China - Yang Wang; Khemaradee Masingboon; Chintana Wacharasin (Belitung Nursing Journal)
Background: Self-management behaviors can prevent the negative consequences among patients with coronary heart disease (CHD). The reality of patients followed the self-management behaviors rate are unoptimistic.